استجابة صفات التبكير والنمو والإنتاج في محصول القطن للتسميد العضوي والمعدني(b) (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في مركز البحوث العلمية الزراعية في الغاب وهدف البحث إلى دراسة استجابة صفات التبكير والنمو والإنتاج في محصول القطن للتسميد المعدني وللتسميد العضوي بروث البقر وبزرق الدواجن بمعدل 20 طن/هـ لكل نوع ، وأضيفت الأسمدة المعدنية بمعدل(490 كغ/هـ يوريا و120 كغ/هـ سلفات البوتاسيوم) وبيّنت الدراسة تفوق معاملتي زرق الدواجن والتسميد المعدني معنوياً في طول الساق ومساحة المسطح الورقي في مرحلة تفتح الجوزات، في حين لم تلحظ فروق معنوية بين هاتين المعاملتين في الصفات المذكورة أعلاه، كما تفوقت كافة المعاملات معنوياً على الشاهد(بدون تسميد) في الإنتاجية خلال الموسمين الزراعيين. This research was carried out in AI-Ghab Agricultural Scientific Research Center. The research goal to study Responding of earliness characteristic, growth and yield of cotton crop to mineral and organic fertilizers by using cow manure and poultry mute. They were added at the rates: 490 kg/ha Urea with 120 kg/ha Sulfate potassium and 20 ton/ha for each kind of organic fertilizer. The use of poultry mute and mineral fertilizers resulted in higher stem height, leafs area (LA) at boll blossoming stage. However few differences were found in same characteristics when comparing the use of poultry mute and mineral fertilizers. This study demonstrated that the use of organic or mineral fertilizers produced higher yield of seed cotton comparing with control in two agricultural seasons.